Empowerment and health care access barriers among currently married women in Myanmar - Nang Mie Mie Htun; Zar Lwin Hnin; Win Khaing (BMC, 2021)
Abstract Background Although Myanmar is moving to attain UHC in 2030, health care utilization indicators are still low, especially among women. Women's health outcomes are determined by the lack of access to health care, and many factors influence this condition. The objective of the present work was to identify the association between women's empowerment and barriers to accessing health care among currently married women in Myanmar. Method We performed a secondary analysis using the Myanmar Demographic and Health Survey (2015-16), including 7759 currently married women aged 15-49 years. The outcome variable, barriers to accessing health care, were asked about in terms of whether the respondent faced barriers to getting permission to go, getting money to go, the distance to the health facility, and not wanting to go alone. The variables were recoded into zero, one, and more than one barrier. After performing the exploratory factor analysis for women's empowerment indicators (decision-making power and disagreement to justification to wife-beating), a multinomial logistic regression was carried out. Results Among currently married women, 48% experienced no barriers when accessing health care services, 21.9% had one barrier, and 30.1% had more than one barrier. After the exploratory factor analysis, scores were recoded into three levels. Women with low and middle empowerment had 1.5 odds (AOR 1.5, 95% CI: 1.2-1.8) and 1.5 odds (AOR 1.5, 95% CI: 1.3-1.9), respectively, to have barriers to accessing health care when compared to those with high empowerment for one barrier group. For the women who had more than one barrier, women with low empowerment were 1.4 times more likely (AOR 1.4, 95% CI: 1.1-1.7) to experience barriers in comparison to women with high empowerment. The barriers were seen to be reduced in the case of women who had a high level of education, had fewer children, came from rich households, and lived in urban areas. Conclusion When women are more empowered, they tend to face fewer barriers when accessing health care services. This finding could contribute to the policy formulation for reducing health inequity issues by increasing women's empowerment.